Short Communication: Using ITS as a molecular marker for Mangifera species identification in Central Sumatra - FITMAWATI FITMAWATI; IBNA HAYATI; NERY SOFIYANTI (Biodiversitas Journal of Biological Diversity, 2016)
Fitmawati, Hayati I, Sofiyanti N. 2016. Using ITS as a molecular marker for Mangifera species identification in Central Sumatra. Biodiversitas 17: 653-656. The relationship among Mangifera species in Central Sumatra is currently unclear. Previous molecular studies on these taxa using cpDNA were unable to produce well-resolved phylogenetic trees. In this study, we explored the potential of the ITS sequences as molecular markers for Mangifera species to better resolve the phylogenetic analysis. Parsimony analysis revealed that the common ancestor M. quadrifida as the first species appeared in Central Sumatra. Mangifera sp. which assumed as new species had the longest genetic distance among species examined and may assumed as the most primitive species of Mangifera in Neighbor-Joining analysis. M. sumatrana and M. torquenda were closely related as well as M. foetida and M. odorata. Also, M. indica was closely related to M. kemanga. This finding and the other marker of cpDNA such as trnL-F and rbcL gene may suggest a possibility to revision in the latest Mangifera classification based on morphological character. Our results also revealed and support the genus Mangifera is a monophyletic group.